Anthropometric Analysis between Naso-aural Inclination and Their Correlation in Bangladeshi Buddhist Rakhain Ethnic Females (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Naso-aural Inclination most prominent structure of the face, influencing facial appearance and profile.Objective: The aim of the study was to describe anthropometric analysis between naso-aural inclination and their correlation in Bangladeshi Buddhist Rakhain Ethnic females.Methodology: This cross-sectional observational study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2011 to December 2011 for a period of one (01) year. Adult healthy Bangladeshi Buddhist Rakhain females in the age group of 18 to 30 years were included as study population. Standard of normative facial anthropometric values related to nose inclination and ear inclination were measured.Result: A total number of 100 adult healthy Bangladeshi Buddhist Rakhain females were recruited for this study. The mean nose inclination was 29.85±5.59 degree and ear inclination left was 11.93±3.44 degree.Conclusion: In conclusion the standard of normative facial anthropometric values related to nose inclination is significantly greater than ear inclination among the Bangladeshi Buddhist Rakhain females.Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):132-135